TERMINALS FOR MULTIMODAL TRANSPORTATION OF DANGEROUS GOODS BY RAIL - Babin, Matej (Doprava a spoje, 2012)
The industrial plants are producing many kinds of materials which need special conditions. The intermodal transportation with swift transport mode changes growing much faster than the other modes. But this type of transportation depends on terminals. This article is focused on terminals for dangerous goods.